OPTIMASI POLIVINILPIROLIDON DAN CARBOPOL PADA SEDIAAN PATCH DISPERSI PADAT PIROKSIKAM - Dwi Nurahmanto; Friska Wira Sabrina; Lidya Ameliana (Jurnal Ilmiah Manuntung, 2017)
Piroxicam, a non steroidal anti inflammatory drugs (NSAID), is an oxicam derivative which can be used for treatment of various rheumatic diseases, such as rheumatoid arthritis and osteoarthritis. Piroxicam patch is an affective approach evading piroxicam’s side effect such as peptic ulcer and first pass metabolism. One of the patch components is polymer that the function is to control the speed of drug release from the patch. The aims of this study were to determine the optimum formula of a combination of polyvinylpyrolidone (PVP) and Carbopol to % moisture content (MC) and the flux release in solid dispersion piroxicam patch using Simplex Lattice Design. Piroxicam was prepared in the form of a solid dispersion in PEG 4000 to increase its solubility. The design formula of solid dispersion piroxicam patch made with the ratio PVP : Carbopol, that were 1 : 0; 0.5 : 0.5; 0 : 1. The optimum formula was chosen with the ratio PVP : Carbopol, 1: 0, which gave the best result of % MC and flux release. The result of % MC was 6.91% and the result of flux release was 35.543 µg/cm2.menit1/2.